PERSEPSI MASYARAKAT TERHADAP RENCANA PEMBENTUKAN DAERAH OTONOMI BARU (DOB) KABUPATEN BANGKA UTARA TAHUN 2021 - Hidayat, Wahyu (Universitas Panca Marga, 2022)
The purpose of this study was to determine differences in public perceptions of the plan to form a new autonomous region in North Bangka Regency. The type of research used is a mixed type of research or what is often called a mixed method. the use of campaign research or mixed methods by combining quantitative and qualitative approaches. Data collection techniques through the distribution of questionnaires and semi-structured interviews. The results showed that the majority of the community stated that the plan to form a new autonomous region for the North Bngka Islands was motivated by the basic interests of the wider community and aimed at increasing the span of control of the central government in serving the community. However, despite this there is another perception that the plan to form a new autonomous region for Bangka Utra Regency is motivated by the interests of only a few local political elites. In addition, the Belinyu-Riau Silip community agreed to carry out the division of the New Autonomy for the North Bangka Islands Regency. This perception is caused by various reasons, including the formation of new districts which will create new jobs, the expansion of North Bangka Regency can open new jobs, can accelerate regional development which will bring regional progress. In addition, the majority of the community also stated that the Belinyu and Riau Silip sub-districts were worthy as new autonomous regions and the expansion of North Bangka Regency would be realized after all the requirements were approved and approved by the government